2017
DOI: 10.1016/j.ygyno.2017.07.119
|View full text |Cite
|
Sign up to set email alerts
|

Extent of lymphovascular space invasion may predict lymph node metastasis in uterine serous carcinoma

Abstract: Objectives Emerging evidence suggests that extent of lymphovascular space invasion (LVSI) predicts for risk of lymph node metastasis in endometrioid uterine cancers. However, this correlation remains unknown in the setting of uterine serous carcinoma (USC). We sought to examine the association between extent of LVSI and other histopathologic characteristics with risk of nodal metastasis for women with USC. Materials/Methods Pathological data from all cases of uterine serous carcinoma between July 1998 to Jul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 29 publications
2
4
0
Order By: Relevance
“…While PFS was unaffected, patients with stage I USC and LVSI had considerably worse OS, with a 2.7 times higher risk of death. This is consistent with recent literature suggesting that LVSI is an important predictor of advanced disease and LVSI an independent prognostic factor associated with worse OS[1214]. The presence of LVSI in early stage disease may further change the management recommendations for adjuvant RT in patients who would previously have been recommended vaginal brachytherapy alone.…”
Section: Discussionsupporting
confidence: 90%
“…While PFS was unaffected, patients with stage I USC and LVSI had considerably worse OS, with a 2.7 times higher risk of death. This is consistent with recent literature suggesting that LVSI is an important predictor of advanced disease and LVSI an independent prognostic factor associated with worse OS[1214]. The presence of LVSI in early stage disease may further change the management recommendations for adjuvant RT in patients who would previously have been recommended vaginal brachytherapy alone.…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies corroborate that lymph node metastases constitute a strong prognostic factor in BCa [29,30]. Mechanistic investigations highlight that lymphovascular invasion may be an important predictor for lymph node metastasis in multiple cancer types [31][32][33]. The present study reveals a significant increase in LINC00336 expression level in BCa patients with vascular invasion.…”
Section: Discussionsupporting
confidence: 87%
“…Several studies have shown that the extent of LVSI is clinically relevant and can be used to improve the stratification of patients with intermediate/high-risk and high-risk EC 9,10,19. Moreover, introducing the concept of measuring the extent of LVSI resulted in pathologists reporting the extent of LVSI using a semiquantitative approach (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…high-risk EC (9,10,19). Moreover, introducing the concept of measuring the extent of LVSI resulted in pathologists reporting the extent of LVSI using a semiquantitative approach (i.e.…”
Section: Defining Substantial Lvsi In Ecmentioning
confidence: 99%
See 1 more Smart Citation